Standarisasi Observer OSCE dengan Rubrik dan Multivideo - Ide Pustaka Setiawan; Noviarina Kurniawati; Rr. Siti Rokhmah Projosasmito (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2012)
Background: One of the factors influencing the validity and reliability of the assessment is the standardization of the observers in assessing students’ performance. A recent study by Setiawan (2011) found that there is differences in the standard of assessment used by general practitioners and specialized doctors in assessing students in OSCE.7 These differences are considered to be harmful for the students, therefore needs to be improved. Several training methods are developed to overcome the problem. This study aims to assess whether rubric and multi video can be used as a means of standardization of OSCE observers.Method: This was an experimental action research. The instruments used in this study were checklist, rubric, and video recording of students doing OSCE (n=5), which further be called multi-video. The subjects of the study were the OSCE observers in station Integrated Patient Management (IPM) who were divided into control and treatment group. The subjects assessed students’ performance from the multi-video in two data collection sessions. In the first session, both control and treatment group used checklist for assessing the multi-video. Furthermore in the second session, the control group did as the first data collection session, while the treatment group used checklist and rubric for assessing the multivideo. The result of which compared and tested using independent sample t-test.Results: As many as 33 observers, which consists of 23 general practitioners (GP) and 10 specialized doctors (SP), participated in the first data collection session. In the second data collection session, 28 observers consist of 20 GPs and 8 SPs participated. The result of the first data collection session, which used only checklist as an instrument, showed a significant difference in the standard of assessment used by the GPS and SPs (p<0.05), whereas the second data collection session, which used rubric as an additional instrument for the treatment group, showed no significant difference between GPs and SPs in the standard of assessment (p>0.05).Conclusion: Rubrics and multi video can be used as a means of standardization of OSCE observer in assessing students’ performance.